EFFICACY OF MICROBIAL PHYTASE AT DIFFERENT LEVELS ON GROWTH PERFORMANCE AND MINERAL AVAILABILITY IN BROILER CHICKEN - Saima; M. Z. U. Khan; M. A. Jabbar; M. Ijaz; M. A. Qadeer (Journal of Animal and Plant Sciences, 2009)
Key words: phytase, broiler, phosphorus, calcium, magnesium ) at different levels on growth performance and mineral availability in broiler chicks fed a low (0.35%) Phosphorus (P) diet. Four levels of microbial phytase (0, 250, 500 and 750 U / kg diet) were added to diets containing M.E. 3000 Kcal/kg and CP 21 %. Phytase supplementation increased (P<0.05) body weight, feed intake, FCR and dressing percentage at 28 day. Supplementation of phytase @ 500 U/kg diet to the low phasphorous diet significantly (P<0.05) improved toe ash percentage. Microbial phytase improved (P<0.05) apparent availability of P, Ca, and Mg. Supplementation of phytase @ 250 U/kg diet was the most economical as cost/kg live weight was lesser than 500 and 750 phytase U/kg diet supplementation. The results showed that microbial phytase supplementation to a low-P diet improved growth performance and apparent mineral availability in broiler chickens.
Keywords: phytase; broiler; phosphorus; calcium; magnesium